Field-Oriented Control of PMSMs within CPU-Constrained Applications - Firmware implementation of an FOC-based control strategy, focusing on robust CPU interrupt handling - Logren, Anders; Johansson, Linus (My University, 2024)
Abstract Efficient control of Permanent Magnet Synchronous Motors (PMSMs) is central for a wide range of applications, where Field-Oriented Control (FOC) is a commonly used control method. In embedded systems where computational resources are constrained, implementing reliable and efficient FOC can be challenging. Particularly when higher-priority tasks occupy the CPU, thereby interfering with the motor control. Ensuring smooth rotation and constant torque production is crucial regardless if the CPU is available for computing new motor control signals or not. This thesis proposes and explores an FOC-based strategy to ensure efficient control of PMSMs within CPU-constrained applications, focusing on robust interrupt handling to maintain motor performance during various operating conditions. The strategy involves pre-computing future control signals and storing them in memory so that, if closed-loop control is interrupted, the CPU peripherals can switch to open-loop control and output the pre-computed signals. The implemented strategy proved successful at maintaining the angular velocity during interrupts using openloop control, regardless of when they occur and their longevity. During interrupts, the produced torque fluctuates and the power consumption increases, but stability is maintained as long as the operating conditions remain unchanged.
Keywords: Keywords: Permanent Magnet Synchronous Motor (PMSM), Field-Oriented Control (FOC), Interrupt handling